Enhancing adherence to diet therapy and fluid restrictions in hemodialysis patients: a study using the information-motivation-behavioral skills model - Zulhikmah S Hi Arsan; Elly Lilianty Sjattar; Rosyidah Arafat (PAGEPress Publications, 2024)
A common issue faced by many patients undergoing the Hemodialysis (HD) is non-compliance with diet therapy and fluid intake limitation. To address this issue, the educational model aims to change the required behavior of patients. The Information Motivation Behavior Skill (IMB) model is a behavioral intervention designed to promote behavior change in various situations. This study sought to assess how well the IMB educational model supports adherence to diet therapy and fluid restrictions in patients receiving HD. This study was carried out in the HD departments. It was a quasi-experimental study featuring a pretest and posttest design with a control group involving 80 patients. The participants were split into an intervention group that received education based on the  Information Motivation Behavior Skill model(n = 40) and a control group that received standard hospital education according to standard operating procedures (n = 40). After eight dialysis sessions over a period not exceeding four weeks, participants were evaluated for adherence to diet therapy and fluid restrictions. Significant change in diet therapy and fluid restriction in the intervention group with the P-value of 0.001. In the control group, there is a significant change in diet therapy and fluid restriction with P-values of 0.005 and 0.002. There are no significant differences between the intervention and control groups in the pre-test for diet therapy and fluid restriction, with P-values of 0.221 and 0.146. However, in the post-test, there are significant differences between the intervention and control groups, with a P-value of 0.001. The Information Motivation Behavior Skill model of education shows great promise in promoting adherence to diet therapy and fluid restrictions.